Regional Development of Human Rights in South Asia - Dhital, Anjana (Kathmandu School of Law Review, 2021)
Various human rights initiatives and developments have emerged in South Asia in the past few years. These initiatives have been taken at the regional as well as national level. However, there exist various challenges because of which this region still lacks a regional human rights mechanism unlike any other region of the world. Thus, this paper explores the recent developments of human rights in South Asia. It studies the development of human rights in each South Asian state particularly. Further, this paper analyzes the possible causative factors behind the slow pace of human rights development in South Asia alongside the failure to develop a regional human rights instrument. The paper does not address the initiatives taken by non-governmental bodies or civil societies working in South Asia to develop the human rights perspectives. Only the governmental and inter-governmental measures have been taken into consideration.